2018
DOI: 10.9734/jammr/2018/42584
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Serum Calcium Levels between Pre-eclamptic and Normotensive Singleton Pregnancies in Federal Medical Centre, Owerri

Abstract: Aim:To compare the serum level of calcium between pre-eclamptic and normotensive pregnant women carrying single foetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Managing obstetric hemorrhage effectively often necessitates prompt and targeted interventions, with blood transfusions playing a pivotal role in stabilizing the patient and preventing severe complications. [15][16][17][18][19][20][21][22][23] Postpartum hemorrhage resulting from uterine atony, a failure of the uterus to contract effectively after childbirth, is one of the most common causes of excessive bleeding. Transfusions are often…”
Section: Indications For Blood Transfusions During Pregnancy Obstetri...mentioning
confidence: 99%
“…Managing obstetric hemorrhage effectively often necessitates prompt and targeted interventions, with blood transfusions playing a pivotal role in stabilizing the patient and preventing severe complications. [15][16][17][18][19][20][21][22][23] Postpartum hemorrhage resulting from uterine atony, a failure of the uterus to contract effectively after childbirth, is one of the most common causes of excessive bleeding. Transfusions are often…”
Section: Indications For Blood Transfusions During Pregnancy Obstetri...mentioning
confidence: 99%
“…Observations from both epidemiological and clinical studies have suggested that the pathological process of coronary artery disease like atherosclerosis begins in neonate. The aortas of children as young as 3-4 years age often contain intimal lipid deposits, commonly called "fatty streaks" [4]. These aortic fatty streaks increase in extent rapidly during the second decade of life and similar lesions begin to appear in the coronary arteries in the latter part of second decade.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in cytokine profiles, shifts in adaptive immune responses, and the involvement of regulatory T cells post-transfusion represent key aspects that demand elucidation.Amidst the scientific curiosity lies the clinical imperative-deciphering the consequences of altered maternal immunity on fetal and neonatal health, as well as obstetric outcomes [15]. An in-depth assessment of risks, benefits, and associated complications stemming from blood transfusions during pregnancy will be intricately woven into our exploration [16][17][18][19][20][21][22][23]. While considerable strides have been made in unraveling these complexities, gaps in understanding persist.…”
Section: Introductionmentioning
confidence: 99%